Analisis Kritis terhadap Konsep Linguistik Tradisional : Sebuah Kajian Teoretis - Christina Purwanti; I Nengah Suandi; Ida Bagus Putrayasa (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
Traditional linguistics has been an important foundation in language studies for decades. However, with the development of the times and technological advances, traditional linguistics has faced challenges and criticism from various parties. The purpose of this study is to critically analyze traditional linguistics, identify advantages and disadvantages, and its relationship to culture as an inseparable part of traditional linguistics. This study uses a qualitative approach to deeply understand traditional linguistics through library research by analyzing various sources of literature relevant to traditional linguistics and various journals directly related to traditional linguistics. The results of the study indicate that traditional linguistics has advantages and disadvantages. It is hoped that this study can be a reference for other researchers who are interested in the topic of traditional linguistics to better understand language and culture.